Prospects of Using Early Neutral Evaluation in Case Management of Complex Civil Cases in Malaysia - Zakiyy, Norman; Hassan, Kamal Halili (European Journal of Economics and Business Studies, 2015)
In Malaysia, pretrial case management has been made an integral part of the litigation process since it is designed to manage cases systematically and within strict deadlines. However, dealing with the evaluative value of complex cases might not be easy, especially for the inexperienced lawyers and some judges who are not familiar with certain areas of law. This study proposes the use of early neutral evaluation for resolving complex civil cases in Malaysia during pretrial case management. Thus, this study sought to examine whether early neutral evaluation can be used effectively to identify issues at the earliest possible time to ensure early disposal or settlement of civil cases. Therefore, the objectives of this study are; first, to explore the viability of introducing an early neutral evaluation program during case management under Malaysia Rules of Court 2012; and secondly to evaluate the potential of adopting an early neutral evaluation programme in Malaysia. The finding shows that early neutral evaluation is consistent to the practice of case management under the Malaysian Rules of Court 2012. Although the Malaysia Rules of Court 2012 provides an opportunity for the adaptation of Early Neutral Evaluation, the introduction and sustainability of such programme would depend largely on a more in-depth study relating to financial resources, readiness of disputants, future goals and expectations of the Malaysian judiciary; and commitment of various stakeholders of the justice system. This study is expected to enrich present literature relating to civil procedure and also provide an overview on possible amendments to current procedural court rules particularly in Asian countries.
Keywords: Early neutral evaluation, pretrial case management, complex civil cases, Malaysia